Dialectic relationship between art and life in Jahza Albrmaki's poetry (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2020)
The poet is an original artist, he find himself in parallels with society , as if the community is different from him, contradicts his visions, the argument between the poet and his community became an argument of a special kind. Art and life are bi-dialectic, Jahza paints its expressions with creative forms, it is duality to existence and fading , death and vanishing, the poet converts existential elements to things to make in the service of art . Hence, this research presents the dialectic of the relationship between art and life. In poetry poet of the Abbasid poets, Jahza Albrmaky, it talks about Jahza's relationship with the argument, and the political and social function, and hence psychological function , and the research ends with a conclusion that includes the findings. الشاعر فنان مبدع ، يجد نفسه في توازٍ مع المجتمع ، وكأن المجتمع يجادله ويخالفه ، ويناقض رؤاه ، ليغدو الجدل بين الشاعر ومجتمعه جدلاً من نوع خاص . والفن والحياة ثنائية جدلية يرسم جحظة تعابيرها بلغة إبداعية ، فهي ثنائية الوجود والتلاشي ، الموت والفناء ، والشاعر يُشيِّئ العناصر الوجودية ليجعلها في خدمة الفن . ومن هنا، جاء هذا البحث ليعرض العلاقة بين الفن والحياة في شعر شاعر من شعراء العصر العباسي هو جحظة البرمكي ، والوظيفتين اللتين يقوم بهما شعر جحظة ، وهما الوظيفة السياسية والاجتماعية، ومن ثم الوظيفة النفسية ، وينتهي البحث إلى خاتمة تتضمن النتائج التي خَلُص إليها .